DINAMIKA INTERAKSI ANTARA GERAKAN DAN INSTITUSI. Gerakan Koperasi Kredit (dapat) Menjiwai Gereja dan Negara - George Ludwig Kirchberger (Institut Filsafat dan Teknologi Kreatif Ledalero, 2014)
This essay looks at the dynamics between movement and institution, where each movement has to ripen in an institution and each institution has to be loosened again and again by new movements and inspirations. The author wishes to outline the dynamics between movement and institution by focusing on the credit union movement. At the beginning the development of the Church from a charismatic movement to an institution is outlined, which in time became extremely rigid. Then, the industrial revolution in the 19 century is looked at with its spirit of liberalism which produced the plight of the workers, which in turn triggered socialist movements which to overcome their plight by changing society radically. The appearance of the social teaching of the Church is seen as an effort to overcome the impasse of these two forces in the industrial revolution. On this background appeared the credit union movement, which embodied a number of the fundamental principles of the social teaching of the Church and is able to become an agent to loosen the structure of the Church hierarchy and support efforts in the country to hold back neo-liberalism and nurture democracy. In taking up the case of the largest credit union on Flores Island, the essay shows how the CU itself lies between the tension between movement and institutionalisation, while pointing out what needs to be done that this tension is maintained creatively, so that the CU is able to offer its spirit to the Church, and support democratisation in the country. Kata-kata kunci: credit union, gerakan, Gereja, koperasi, institusi, struktur